In separate places exploring the motivations of long-distance couples in engaging in sexting during COVID-19 lockdowns - Aquiatan, Paul Alfred Cebreros; Manapat, Marc Vincent Bolok; Tan, Lester Niel Acopiado (2023)
The study investigates the development of sexting engagement in the setting of distant relationships during the pandemic, as well as the motivations and benefits of continued sexting involvement. Previous studies on sexting, and very few studies focused on the motivations and positive outcomes it may contribute to relationships. The current study applied the Social Exchange Theory to examine how individuals comprehend why they engage in sexting activities, recognize the benefits and drawbacks of the activity, and investigate why they continue to participate in it. Semi-structured interviews were conducted with 3 male and 3 female participants, and the data was analyzed using Interpretative Phenomenological Analysis.